1985
DOI: 10.1002/aic.690310609
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modeling of catalytic converter lightoff. Part II: Model verification by engine‐dynamometer experiments

Abstract: A transient mathematical model has been developed which describes the behavior of packed-bed catalytic converters during warmup. Model predictions agree very well with the results of enginedynamometer experiments for three Ptalumina catalysts of widely different properties, thus demonstrating the validity of the model. General Motors Research LaboratoriesWarren, MI 48090 SCOPEUnited States federal regulations of automobile exhaust emissions are based on pollutant emissions measured while driving a vehicle over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 19 publications
(32 reference statements)
1
37
0
Order By: Relevance
“…has been studied extensively in the past over several catalyst formulations [94] and is considered to proceed according L-H mechanism, where adsorbed CO and oxygen react in a rate-determining surface step [95] . The detailed reaction mechanism is not part of this study and can be found elsewhere [96] .…”
Section: Co R E a C T I O N Smentioning
confidence: 99%
See 4 more Smart Citations
“…has been studied extensively in the past over several catalyst formulations [94] and is considered to proceed according L-H mechanism, where adsorbed CO and oxygen react in a rate-determining surface step [95] . The detailed reaction mechanism is not part of this study and can be found elsewhere [96] .…”
Section: Co R E a C T I O N Smentioning
confidence: 99%
“…The model of this thesis originates from the milestone works of Voltz [93] and Oh and Cavendish [94] and belongs to a large group of models sharing similar practically remained unsolved while the storage submodels were identified to be responsible for the major inaccuracies of the model.…”
Section: 2 C O N C L U S I O N Smentioning
confidence: 99%
See 3 more Smart Citations